472 Low-Field Portable Magnetic Resonance Imaging for Bedside Evaluation of Ischemic Stroke in Post-Thrombectomy Patients. (April 2023) - Sujijantarat, Nanthiya; Koo, Andrew B.; Jambour, Ivan; Malhotra, Ajay; Crawford, Anna; Mazurek, Mercy; Parasuram, Nethra; Chavva, Isha; Sze, Gordon; Renado, Daniela; Antonios, Joseph Paul; Elsamadicy, Aladine A.; et al.
Abstract : INTRODUCTION: Timely brain imaging is an essential component in clinical decision-making for patients undergoing mechanical thrombectomy (MT). The requirement for controlled access suites for high-field conventional MRI (cMRI) precludes rapid access for examination. In this study, we examined the use of low-field portable MRI (pMRI) in the post-thrombectomy setting. METHODS: Low-field pMRI was used to obtain bedside imaging in patients who underwent MT between December 2021 to April 2022 at Yale-New Haven Hospital.All pMRI exams were conducted in the standard ferromagnetic environment of the IR suite, with clinical and research staff present. Clinical, procedural, and pMRI details were collected. Two neuroradiologists served as blinded raters and evaluated pMRIs and cMRIs independently. If cMRI was not available for comparison, a post-thrombectomy CT was used. RESULTS: A total of 18 patients (61% females, median age 77 years-old [IQR 70-84]) underwent pMRIs in the IR suite after MT. MT was performed with a median access to revascularization time of 15 minutes [IQR 8-19], and with a TICI score of 2B and above in all patients. The median pMRI examination time was 30 minutes [IQR 13-32]. Thirteen patients (72.2%) had cMRI within 72 hours post-thrombectomy, while 4 who did not have cMRI (80%) underwent CT. Blinded raters correctly identified the presence of stroke on pMRI in all cases. Intracranial hemorrhage was identified on pMRI in 33.3% of the cases. The median infarct volume was 5.7 cc [IQR 3.83-15.43] on pMRI and 4.37 cc [IQR 0.66-16.5] on cMRI or post-thrombectomy CT. There were no adverse events related to the examination. CONCLUSIONS: The use of low-field pMRI is feasible in a post-thrombectomy setting and can enable timely identification of ischemic changes at bedside. Low-field pMRI may be helpful in acquiring time-sensitive brain imaging which may impact clinical decision-making post-thrombectomy.